RUMAH ADAT DI PESISIR SELATAN PULAU SERAM, MALUKU TINJAUAN AWAL ETNOARKEOLOGI - Lucas Wattimena (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2014)
Ethnoarchaeology Research is a reconstruction of archaeological context in answering the society of human life in the past, present, and future. The objective of the study is to provide support of anthropological data for understanding archaeological phenomena. One aspect of ethnoarchaeology is the indigenous house on the south coast of Ceram Island in Central Mollucas regency, Mollucas Province. The study aims to understand the prehistoric charactheristic contained in the indigenous house of Nuaulu People in South Ceram. It uses qualitative approach and qualitative analysis. The results showed that the prehistoric characteristics of the indigenous house of Nuaulu People located on the southern coast of Seram island are found in its shape (on poles), settlement patterns, and structure.